Reference Values for and Correlation Analysis of the Anogenital Distance of Chinese Han Full-Term Singleton Neonates - Cao, Wei; Ding, Xiaowei; Dong, Zhiya; Tang, Haiting (Frontiers in Pediatrics, 2022)
Background: Anogenital distance (AGD) is a biomarker used for the evaluation of fetal androgen action. The disruption of fetal androgen action can affect the development of the reproductive system and adversely affect future reproductive functions. However, AGD may differ by race. Currently, there is a lack of data regarding the evaluation of AGD in large Han Chinese samples. Objective: AGD for neonates in Shanghai, China, was measured, and relevant factors that influenced AGD were analyzed. Methods: The AGD of full-term singleton neonates was measured within 3 days of birth, and the results were grouped according to gestational age and body weight at birth. In addition, relevant factors that influenced AGD were investigated. Results: A total of 1867 full-term singleton neonates were enrolled in this study. All the neonates were Han Chinese; among them, 986 were male, and 881 were female. Male AGD was 23.18±3.17 mm, and female AGD was 11.65±1.53 mm. Male AGD was 1.99 times longer than female AGD. With the increase in gestational age and body weight, AGD gradually increased. AGD was correlated with gestational age, body weight, and head circumference. The correlation between body weight at birth and AGD was highly significant. Conclusion: This study, for the first time, reported AGD measurement data for Chinese Han neonates. The results indicated that AGD was correlated with gestational age, body weight, and head circumference. The correlation between body weight at birth and AGD was highly significant.